A Study on Determination and Implementation of Operation Theatre Management System in a Private Hospital, Trichy: A Six Sigma Approach (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The study aims in increasing the number of surgeries with the available resources in the operation theatre which ultimately improves the efficiency and effectiveness of operation theatre. Efficiency rate is calculated multiplying the availability of operation theatre, Number of scheduled surgeries and success rate of surgeries. This formula is commonly accepted in calculating the efficiency rate among Industrial sectors. The study covers the activities involved from patients entering pre operation theatre to transferring them to post operation theatre i.e. from admission to discharge process of operation theatre. Methodology adopted in this study is Six Sigma. The Defect per million opportunities analysis reveals that the existing sigma level is 2.6 and the existing efficiency rate is 54.5 percent. It was found that the risk priority number was high in the assessment and preparation of surgery process in which missing of pre-assessment and failure to give timely request for investigation has been identified as the failure modes. This leads to increase in average length of stay which is caused by postponement and cancellation of surgeries; this ultimately leads to reduction in productivity. The vital few items are found to be poor pre admission procedure, in adequacy in manpower, patient delay, drugs delay and slow turnaround time. Improving the efficiency by finding solutions to the root causes leading to substantial improvement in Quality of service can be achieved through Six Sigma approach which is one of the Total quality management concepts and methodologies.